Implementasi Program Tahfiz Al-Qur’an di SD Al Wathoniyah 9 Jakarta - Muhamad Hapiz; Mugiyono Mugiyono (Journal on Education, 2024)
This research aims to find out the implementation of Al Qur’an’s tahfiz program in Al Wathoniyah 9, Jakarta. The aspects studied include planning aspects, steps, and implementation obstacles and solutions. The purposes of this survey are: a. to analyze the implementation of the Tahfizh Al Qur’an program in Al Wathoniyah 9 Jakarta; b. to know the steps in the application of the Tahfiz Al Quran program in Al Watoniyah 9 Jakart; and c. to find out the obstacles and solutions in implementing the Tahfish Al Quran program in Al Wathoniah 9 Jakarta. This research uses a qualitative approach with a case study approach at Al Wathoniyah 9, Jakarta. The data obtained from this research was obtained through observations, interviews, and documentation studies. Based on the data, the researchers used descriptive analysis, i.e., by describing or describing what the findings in the field related to the implementation of Al Qur’an’s tahfiz program at Al Wathoniyah 9 Jakarta. The results of the research indicate that the application of Al Quran’s Tahfiz program in Al Wathoniyah 9 Yakarta includes: 1) Planning, implementation, and Al Qur'an tahfis program done in a structured manner, which includes program setting, selecting pupils, setting time and material, making a reading book, and making an assessment of pupils. The researchers concluded that the planning was done well. Everything's on top of it. Thus, in the first instance, the teaching of the Scriptures and the teachings of the apostles, and in the second instance, the prophecy of the Bible, the Bible and the Bible are the principles of teaching, teaching, and teaching. The obstacles experienced were so minimal that the researchers could conclude that the study went well and worked.